La Investigación histórico-archivística en los Procesos de Canonización - Salvia, Ernesto R. (Anuario argentino de derecho canonico, 2016)
In diocesan canonization processes it is necessary to configure a Commission of experts in history and filing devoted to collect the whole documentation and testimonies to make a written report about the servant of God. It is well noted in this article the importance of team working in that Commission, and also of the specific developed tasks in files. Elementary guidance about the steps to follow to accomplishing a well done presentation of the historical report about the servant of God is also provided